Device characteristics of carbon nanotube transistor fabricated by direct growth method - Inami, Nobuhito; Mohamed, Mohd Ambri; Shikoh, Eiji; Fujiwara, Akihiko (American Institute of Physics Inc., 2008)
We have fabricated carbon nanotube CNT ﬁeld-effect transistors FETs by direct growth of single-wall CNTs between the source and drain electrodes, and investigated their device characteristics. The FETs show ambipolar operation. The temperature and bias voltage dependence of device characteristics are consistent with device operation of the Schottky-type FET. The carrier injection barrier heights for both the electron and hole carriers show small values of 17– 74 meV, without any additional speciﬁc treatment after device fabrication.